Development of antimicrobial formulation based on essential oils and gamma irradiation to increase the shelf life of boneless chicken thighs. (March 2022) - Shankar, Shiv; Karboune, Salwa; Salmieri, Stephane; Lacroix, Monique
Abstract: The present study illustrates the development of essential oils (EOs) formulation, and boneless chicken thigh samples were treated with the developed EOs formulation and gamma irradiation to increase the shelf life of treated chicken samples. The binary, tertiary, and quaternary combinations of EOs were developed by the broth dilution method and the fractional inhibitory concentration index. The tertiary combinations of EOs, Thyme + Cannelle + Oregano, showed the best result and exhibited additive (AD) effect against S. enterica, S aureus, and E. coli. The shelf life of the chicken sample increased by 3 days and 8 days when treated by Thyme + Cannelle + Oregano EOs and γ-irradiation, respectively. However, when chicken samples were treated with the combinations of EOs formulations and γ-irradiation, the shelf life of the chicken sample increased by 14 days. The results showed that the combination of EOs treatment with a low dose of γ-irradiation could be used to increase the shelf life of treated food. Highlights: FIC values of binary, tertiary, and quaternary combinations of EOs were determined. Tertiary combinations of Thyme + Cannelle + Oregano EOs showed additive effect. EOs formulation increased chicken shelf life by 3 days. Treatment with γ-irradiation increased the shelf life of the chicken by 8 days. The combination of EOs and γ-irradiation increased chicken shelf life by 14 days.